A revision of the wolf spider genus Diapontia Keyserling, and the relationships of the subfamily Sosippinae (Araneae: Lycosidae) - Piacentini, Luis Norberto (2017)
The South American genus Diapontia is revised to include nine species: Diapontia uruguayensis Keyserling, 1877 (= Diapontia senescens Mello-Leitão, 1944 syn.n.; D. infausta Mello-Leitão, 1941 syn.n.; D. pourtaleensis Mello-Leitão, 1944 syn.n.; D. albopunctata MelloLeitão, 1941 syn.n.) from northern Paraguay, southeastern Brazil, southern Uruguay, southern to northeastern Argentina and southern Chile; D. niveovittata Mello-Leitão, 1945 from southern Paraguay, north-central Argentina and southern Brazil; D. anfibia (Zapfe-Mann, 1979) comb.n. (= Lycosa artigasi Casanueva, 1980 syn.n.) from central and southern Chile and southwestern Argentina, transferred from Pardosa C.L. Koch, 1847; D. securifera (Tullgren, 1905) comb.n. from northern Chile and northwestern Argentina, transferred from Orinocosa Chamberlin, 1916; D. arapensis (Strand, 1908) comb.n., from Peru, transferred from Hippasella Mello-Leitão, 1944; D. calama sp.n. from northern Chile; D. songotal sp.n. from southern Bolivia; D. chamberlini sp.n. from central and southern Peru; and D. oxapampa sp.n. from northern Peru. The sister-group relationship between Diapontia and Hippasella, and their placement in the subfamily Sosippinae, were supported by phylogenetic analyses based on four molecular markers (28S, 12S, NADH1 and COI), using Bayesian inference and maximum-likelihood. We tested whether DNA barcoding techniques were able to corroborate the identity of four Diapontia species. Diapontia securifera and D. anfibia were successfully identified using COI; however, D. niveovittata and D. uruguayensis were found to share identical haplotypes and thus could not be discriminated.